Project management and viability of the company - Trunk, Aleš (International journal of management, knowledge and learning, 2024)
Purpose: This study investigates the critical role of project management in enhancing a company's operational viability, focusing on a Slovenian automotive industry company as a case study. The research scrutinises the efficiency of project and resource management and its direct correlation with the company's business performance amidst the backdrop of an ever-evolving global market. The study provides concrete evidence of how effective project management can drive business success by delving into specific project examples. Study Design/Methodology/Approach: Adopting a mixed-methods approach, the study encompasses both qualitative and quantitative analyses. A case study of a selected company, which recently embarked on significant organisational restructuring to accommodate growing project demands, forms the core of our research. The study delves into the optimisation of project resources and its impact on the company's competitiveness and market position through detailed analysis, interviews, surveys, and comparing project management models before and after reorganisation. We employ descriptive statistics, inferential statistics, and content analysis to ensure a comprehensive understanding of the data. Findings: The research reveals that systematic project management significantly contributes to the company's efficiency and competitiveness. Key findings include increased project team efficiency, cost reduction, and improved global market competitiveness. Additionally, the study underscores the importance of a structured project office and robust resource management in attaining and surpassing projected business outcomes. Concrete examples from specific projects illustrate how challenges were addressed and resolved, providing practical insights for similar contexts. Originality/Value: This study contributes original insights into the strategic implementation of project management in a competitive industrial sector. By integrating theoretical knowledge with practical applications within the automotive industry, the research offers valuable perspectives on improving project management practices to enhance organisational viability and performance. Furthermore, the study's findings on resource optimisation and strategic project management provide a foundational framework for future research and practical applications in similar industrial contexts. The detailed case study examples enhance the practical relevance of the findings.
Keywords: business performance; management gospodarstva; project management; sposobnost preživetja podjetja; uspešnost poslovanja; viability of the company; vodenje projektov